Family Control and Firm Financial Performance Listed on Indonesia Stock Exchange: The Moderating Role of Foreign Ownership - Pangeran, Perminas (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to examine whether foreign ownership moderates the relationship between family control and financial performance. Based on the purposive sampling technique, this study uses 16 large family companies listed on the Indonesia Stock Exchange (BEI), during 2012-2017. Hypothesis testing using Moderated Regression Analysis (MRA). The results of this study reveal several important things. First, foreign ownership positively moderates the relationship between family control and dividend payments. Second, foreign ownership positively moderates the relationship between family control and profitability. These results suggest that foreign ownership can mitigate the level of expropriation of the wealth of minority shareholders by family owners. In this case, foreign owners are able to suppress the negative effect of family control on profitability and dividend payments.